1996
DOI: 10.1021/bi961658l
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Autoreduction Pathway for the [Fe4S4]3+ Cluster of Mutant Chromatium vinosum High-Potential Iron Proteins. Site-Directed Mutagenesis Studies To Probe the Role of Phenylalanine 66 in Defining the Stability of the [Fe4S4] Center Provide Evidence for Oxidative Degradation via a [Fe3S4] Cluster

Abstract: A number of point mutations of the conserved aromatic residue phenylalanine 66 (Phe66Tyr, -Asn, -Cys, -Ser) in Chromatium vinosum high-potential iron sulfur protein have been examined with the aim of understanding the functional role of this residue. Nonconservative replacements with polar residues have a minimal effect on the midpoint potential of the [Fe4S4]3+/2+ cluster, typically < +25 mV, with a maximum change of +40 mV for Phe66Asn. With the exception of the Phe66Tyr mutant, the oxidized state was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…The oxidized Trx-Fe 4 S 4 cluster is only transiently stable, as evidenced by rapid bleaching of the visible absorbance upon ferricyanide addition, and the disappearance of the g avg Ͼ 2 EPR signal upon prolonged incubation at 4°C. Such cluster degradation has been reported for HiPIPs and is believed to produce reducing equivalents (Fe 2ϩ , S 2Ϫ , and CysSH) (41). While these factors complicate the determination of a redox potential, our observation of complete oxidation upon addition of Ͼ7 equivalents of potassium ferricyanide, and incomplete oxidation at lower concentrations allows us to place a lower bound of ϩ300 mV vs. NHE on the redox potential of Trx-Fe 4 4 S 4 ] cluster in bacterial Fds is Cys-X 2 -Cys-X 2 -Cys with a more remote Cys residue supplying the fourth ligating sulfur center.…”
Section: Discussionmentioning
confidence: 52%
“…The oxidized Trx-Fe 4 S 4 cluster is only transiently stable, as evidenced by rapid bleaching of the visible absorbance upon ferricyanide addition, and the disappearance of the g avg Ͼ 2 EPR signal upon prolonged incubation at 4°C. Such cluster degradation has been reported for HiPIPs and is believed to produce reducing equivalents (Fe 2ϩ , S 2Ϫ , and CysSH) (41). While these factors complicate the determination of a redox potential, our observation of complete oxidation upon addition of Ͼ7 equivalents of potassium ferricyanide, and incomplete oxidation at lower concentrations allows us to place a lower bound of ϩ300 mV vs. NHE on the redox potential of Trx-Fe 4 4 S 4 ] cluster in bacterial Fds is Cys-X 2 -Cys-X 2 -Cys with a more remote Cys residue supplying the fourth ligating sulfur center.…”
Section: Discussionmentioning
confidence: 52%
“…3ϩ/2ϩ, 2ϩ/ϩ, or ϩ/0) or by modulation of the reduction potential (E 0 Ј) of a particular redox couple (7-19). Thus, high potential iron proteins have 3ϩ/2ϩ E 0 Ј ranging from 90 to 450 mV (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)20), while ferredoxins that contain structurally indistinguishable 2ϩ/ϩ clusters have E 0 Ј ranging from Ϫ280 to Ϫ715 mV in different native proteins (10, 21).…”
Section: The Reduction Potential (E 0 ) Of the [4fe-4s]mentioning
confidence: 99%
“…3ϩ/2ϩ, 2ϩ/ϩ, or ϩ/0) or by modulation of the reduction potential (E 0 Ј) of a particular redox couple (7-19). Thus, high potential iron proteins have 3ϩ/2ϩ E 0 Ј ranging from 90 to 450 mV (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)20), while ferredoxins that contain structurally indistinguishable 2ϩ/ϩ clusters have E 0 Ј ranging from Ϫ280 to Ϫ715 mV in different native proteins (10, 21).Both experimental and theoretical research has been directed toward understanding how the polypeptide surrounding the cluster controls the reduction potential. Factors that have been proposed as being important include (a) solvent exposure of the cluster, (b) specific hydrogen bonding networks especially NH-S bonds, (c) the proximity and orientation of protein backbone and side chain dipoles, and/or (d) the proximity of charged residues to the cluster (7,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 However, these studies could not differentiate between IscU functioning as an iron or an iron-sulfur cluster delivery protein. Given our long-standing interest in Fe-S biochemistry and mechanisms of cluster assembly and disassembly, [41][42][43] we initiated a program to compare and contrast the properties of IscU from a variety of sources, including human (Hs ISU), yeast (Schizosaccharomyces pombe, Sp ISU), and a hyperthermophilic bacterium (Thermotoga maritima, Tm IscU). In agreement with Dean and colleagues, 27 we found that IscU coordinates one reductively labile [2Fe-2S] 2+ cluster per monomeric subunit that is stabilized by substitution of a highly conserved aspartate (D37 for Hs ISU and Sp ISU, and D40 for Tm IscU), as judged by Mössbauer, EXAFS, EPR, and UV-vis spectroscopies.…”
Section: Cast Of Characters In Iron-sulfur Cluster Biosynthesismentioning
confidence: 99%